DESAS DESUS INFORMASI HAJI DALAM HUBUNGANNYA DENGAN DAFTAR TUNGGU BAGI CALON JEMAAH HAJI DI KABUPATEN GOWA - Ibrahim Ibrahim; Andi Alimuddin Unde; Muhammad Farid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2015)
Abstract Rumors information Hajj often bring news is not true, circulated from mouth to mouth very quickly and circulated like a snowball throws prospective pilgrims. This research aims to: Knowing the form of rumors circulating among Hajj information prospective hajj congregation waiting list, Knowing acceptance of rumor information of hajj for potential congregation waiting list, find out how patterns of rumor information of hajj for hajj congregation waiting list candidates in Gowa region. This research used a descriptive approach with case studies as a focus of analysis. The technique of collecting data through in-depth interviews, the study of librarianship, observation and physical devices. As for the data analysis done qualitatively-verifikatif with data validation using the technique of triangulation of sources. The research showed the form of the rumor for hajj information related to the waiting list for candidates in Gowa region is a